Thermal and chemical analysis of carbonaceous materials: diesel soot and diesel fuel reactor deposits - Kaminuza, Irénée (Sasol Advanced Fuels Laboratory, 2016)
Methods for the characterisation of fuel-derived carbonaceous materials were assessed. These methods were applied to two such materials, viz. diesel soot and diesel fuel deposits. Diesel soot: Diesel soot, sampled from a commuter bus, was characterised using an array of analytical techniques. Physical and chemical characterisation of diesel soot was conducted with particular interest in the component of soot known as the soluble organic fraction (SOF). The SOF represents adsorbed chemical species and is traditionally obtained via Soxhlet extraction of soot using an organic solvent. Chemical speciation of the SOF was performed using GC-MS analysis. Five solvents (hexane, cyclohexane, toluene, methanol and acetone) were compared with dichloromethane, the most extensively used solvent for the extraction of soot with respect to their ability to extract a variety of species, including polyaromatic hydrocarbons (PAHs) and potential endocrine disrupting molecules, e.g. phthalates. Extraction results suggest that the SOF quantity depends significantly on the extraction solvent. For the soots analysed, SOF ranged between 1.0 and 4. 8 wt %, depending on the solvent used. Moreover, it was shown that polar solvents extracted a greater SOF than non- polar solvents. For PAH extraction the order of efficiency was acetone > methanol > > toluene > hexane > cyclohexane while for esters, including endocrine disrupting phthalates, the order in efficiency was methanol > dichloromethane >acetone > toluene > > hexane > cyclohexane > n-hexane. A suggestion is made that to maximise SOF, sequential extraction should be made. Thermogravimetric analysis revealed a discrepancy between VOF and SOF which was ascribed to the presence of sulfurous and sulfuric acid which were not extracted by the organic solvents investigated Fuel deposits: Fuel was degraded in three reaction vessels, viz. a continuous flow reactor, open glass flask s and closed metal reactors (bombs) in an attempt to synthesise carbonaceous deposits, analogous to those found in diesel injectors. The degradation of four diesel fuels, viz. an EN590 reference diesel, a commercial diesel and two B20 biodiesel blends (rapeseed and soybean methyl esters blended with EN590 diesel), was investigated in the thermo-oxidative temperature regime, i.e. below 300° C.